Status and predictors of medical students’ knowledge and attitude towards palliative care in Jordan: a cross-sectional study - Wejdan Y. Younis; Ayman M. Hamdan-Mansour (BMC Palliative Care, 2024)
Abstract Background Palliative care focuses on the ability of medical students to use their expanded experiences and knowledge; however, basic medical education does not provide adequate knowledge and skills regarding palliative and end-of-life care. This study designed to examine knowledge related to palliative care and attitudes toward dying people among medical students in Jordan. Methods Cross-sectional, descriptive design was used in this study. A total of 404 medical students were recruited using convenience sampling techniques from six medical programs. Data was collected using a self-administered questionnaire in relation to knowledge and attitudes regarding palliative care and dying persons using Palliative Care Assessment Knowledge (PCAK) and Frommelt Attitudes toward Care of the Dying Scale Form B (FATCOD-B). Results Medical students have a moderate level of knowledge related to palliative care in (PCAK) part1 subscale about; pain managing (n = 156, 38.6 %), managing other palliative care symptoms (n = 164, 40.6 %), and in witnesses' family counseling and breaking bad news discussion (n = 178, 44.1 %). However, medical students have inadequate knowledge concerning the palliative care in part-2of the scale. Furthermore, students have positive attitudes towards caring for dying patients with mean score of 108.76 (SD = 8.05). The highest ranked attitude subscales were; Fairs/Malaise (M = 29.03, SD = 4.28), Communication (M = 21.39, SD = 2.51) and Relationship (M = 18.31, SD = 1.55). There was a significant difference in attitudes in relation to gender (t = -5.14, p < 0.001) with higher female mean score (M = 109.97) than males (M = 105.47). Also significant difference found among those who are exposed to Palliative Care and those who are not (t = -6.33, p < 0.001) with higher mean score of those exposed to palliative acre courses (M=298) than those who did not (M=106). Conclusion Improving knowledge and attitudes of medical students regarding palliative and end of life care should be highlighted to medical educators and medical schools need to incorporate palliative and end-of-life care into medical curricula across all levels